Barriers to Student Learning and Participation in an Inclusive School as Perceived by Future Education Professionals - Pilar Arnaiz Sánchez; Remedios de Haro-Rodríguez; Rosa María Maldonado Martínez (Springer, 2019)
Inclusive education represents the way forward to achieving high quality education systems, which are fair and equitable. This paper analyzes the barriers to learning and the current participation of schools in the promotion of inclusion from the perspective of future teaching professionals, specifically, 86 students from three Masters Courses in the Faculty of Education of the University of Murcia. A questionnaire was utilized in order to ascertain their perceptions of the limitations and obstacles present within the school context, the attitudes, the availability of resources and the adequacy of the educational response offered by the educational centres in which they had carried out their teacher training placements, with the aim of improving the future training of other students. A non-experimental narrative method was used. The results show many barriers and obstacles in the educational centres such as a lack of teacher training, which is needed to respond to the needs of all the students, the consideration that the diversity of the students is a problem, physical barriers, underuse of existing resources, as well as an educational response lacking in organizational and didactic strategies which does not take responsibility for a just and inclusive curriculum for all students.